ECONOMIC EFFECT CALCULATION FROM NEW FLAXSEED SOLUTION FOR ROAD DUST SUPPRESSION DURING OPEN PIT MINING IN ALEXEEVSKY CEMENT DEPOSIT IN MORDOVIA. CASE STUDY - Zhulina, Marina (Journal of Applied Engineering Science, 2021)
A method is proposed to reduce dust formation from technological roads during open pit mining. It is suggested to use a solution based on flaxseed cake, instead of only water, for irrigation the technological roads. It can wet the roads more efficiently. The frequency of watering can be significantly decreased, thereby the employees working time can be optimized to reduce harmful effects on health. The costs for oil and fuel also will be decreased. The calculation of costs included the cost of labor, electricity, fuel for the sprinkler, repairs, depreciation and others. Also, a SWOT analysis of the project was performed to justify possible risks, including economic ones, associated with the implementation and application of the proposed method. It was calculated, an economic effect can be achieved in amount of about 1.5 million rubles per year at the Alexeevsky enterprise.
Keywords: dust suppression, open pit mining, technological roads irrigation, calculation of costs, SWOT analysis, economic efficiency